Sosialisasi Transformasi Kantin Sekolah Sehat di SD ‘Aisyiyah 1 Mataram - Aulia Amini; Dwi Kartika Cahyaningtyas; Evi Diliana Rospia; Muthoharoh Muthoharoh; Biantari Alika Maharani (Indonesian Journal Publisher, 2024)
Children's health is the most important aspect in building a strong and high-quality young generation. Good nutrition and healthy eating habits play a central role in the growth and development of children. This community service activity aims to promote the transformation of healthy school canteens at SD 'Aisyiyah 1 Mataram and to introduce the concept of healthy canteens to all parties involved in the education and development of children, including students, teachers, school staff, and parents. The activity begins with identifying needs through an initial survey highlighting the condition of the school canteen and students' eating habits. This includes providing education on the importance of healthy and nutritious food by bringing in nutrition experts for students, teachers, canteen staff, and parents/guardians to enhance understanding of healthy food, balanced diets, and their impact on health. Program evaluation is conducted by measuring changes in knowledge and attitudes through questionnaires distributed before and after the activity. Direct observation is also carried out to see real changes in canteen operations and students' eating habits. The evaluation results show a significant increase in awareness and knowledge about healthy food among students, teachers, and canteen managers. There has been a positive change in the provision of healthy menus in the school canteen. It is hoped that this can become a model for other schools in creating a healthy learning environment that supports the optimal development of children.